Handbook of research on complex dynamic process management : techniques for adaptability in turbulent environments - Wang, Minhong (Hershey, PA : Business Science Reference, 2010)
"This book combines both a managerial and technical view of business process management, providing advanced analysis and concrete approaches for relevant problems, as well as the implications for further studies and practices"--Provided by publisher.
Fakulti Keusahawanan & Perniagaan
Keywords: Industrial management; Management information systems; Workflow -- Management